Antimetastatic Potential of Rhodomyrtone on Human Chondrosarcoma SW1353 Cells. (27th July 2020) - Tayeh, Malatee; Watanapokasin, Ramida
Abstract : Chondrosarcoma is primary bone cancer, with the forceful capacity to cause local invasion and distant metastasis, and has a poor prognosis. Cancer metastasis is a complication of most cancers; it is one of the leading causes of cancer-related death. Rhodomyrtone is a pure compound that has been shown to induce apoptosis and antimetastasis in skin cancer. However, the inhibitory effect of rhodomyrtone on human chondrosarcoma cell metastasis is largely unknown. Effect of rhodomyrtone on cell viability in SW1353 cell was determined by MTT assay. Antimigration, anti-invasion, and antiadhesion were carried out to investigate the antimetastatic potential of rhodomyrtone on SW1353 cells. Gelatin zymography was performed to determine matrix metalloproteinase-2 (MMP-2) and MMP-9 activities. The effect of rhodomyrtone on the underlying mechanisms was performed by Western blot analysis. The results demonstrated that rhodomyrtone reduced cell viability of SW1353 cells at the low concentration (<3 μ g/mL); cell viability was >80%. Rhodomyrtone at the subcytotoxic concentrations (0.5, 1.5, and 3 μ g/mL) significantly inhibited cell migration, invasion, and adhesion of SW1353 cells in a dose-dependent fashion. Protein expression of integrin α v, integrin β 3, and the downstream migratory proteins including focal adhesion kinase (FAK) and the phosphorylation of serine/threonine AKT, Ras, RhoA, Rac1, and Cdc42 were inhibited after treatment with rhodomyrtone. Moreover, we found that rhodomyrtone decreased the protein level of MMP-2 and MMP-9 as well as the enzyme activity in SW1353 cells. Meanwhile, tissue inhibitor of metalloproteinase-1 (TIMP-1) and TIMP-2 expression was increased in a dose-dependent fashion. Besides, rhodomyrtone dramatically inhibited the expression of growth factor receptor-bound protein-2 (GRB2) and the phosphorylated form of extracellular signal regulation kinase1/2 (ERK1/2) and c-Jun N-terminal kinase1/2 (JNK1/2). These results indicated that rhodomyrtone inhibited SW1353 cell migration, invasion, and metastasis by suppressing integrin α v β 3/FAK/AKT/small Rho GTPases pathway as well as downregulation of MMP-2/9 via ERK and JNK signal inhibition. These findings indicate that rhodomyrtone possessed the antimetastasis activity that may be used for antimetastasis therapy in the future.